Evaluation of the Net Wealth in Bulgaria Using Data from the Global Wealth Databook of Shorrocks et al. (2023) - Peshev, Petar (Research Papers, 2024)
This research paper estimates the net wealth of an adult in Bulgaria, using data of Shorrocks et al. (2023). Net wealth per adult has a strong functional relationship with GDP per adult, corresponding on average to four times GDP per adult. Econometric research suggests net wealth per adult equals between 56,989 and 66,373. Net wealth is most sensitive to changes in wealth, in the form of real assets and to a lesser extent, to financial wealth and debt, and to changes in GDP per adult and the rate of change of the elderly population.